#Feminist – naming controversies and celebrating points of connection and joy in current feminisms. (4th May 2022) - Olson, Greta; Lechner, Elisabeth
ABSTRACT: In a dialogue, the authors discuss controversies in feminisms and their hopes for feminist futures. The first sections dismantle oppositional catfight narratives regarding feminisms and highlight the misogynist and transphobic cultural-political work they perform. Feminists and trans activists find common cause in resisting the subordination and control of womxn's and trans persons' bodies. Later sections outline an activist approach to doing feminisms online, while asking participants to keep the capitalist embeddedness of social media in mind. Body-positive activism and body neutrality are explored as strategies of resistance. Rather than adhering to a narrative of opposition, the authors advocate for acknowledging the common ground that shared vulnerability holds for community building and mobilising political agency. Healing and points of joy are sought in connection.